ANALISIS DISKRIMINAN INTRODUKSI TEKNOLOGI BENIH UNGGUL PADI SAWAH DI KABUPATEN LAMPUNG TENGAH - Sutarni, .; Haryono, Dwi; Situmorang, Suryati (Indonesian Journal of Socio Economics)
This research aims to analyze the effect of prime seed of hybrid rice toward seed cost, fertilizer cost, pesticide cost, worker cost, productivity, rice cost, and rice field earnings. This research was conducted in Seputih Raman and Punggur Districts at Central Lampung Regency. Analysis method used multivariate discriminant analysis. Introduction of prime seed technology has significantly effects toward increasing of seed cost, fertilizer cost, pesticide cost, worker cost of hybrid rice field in Central Lampung regency, and  decreasing of rice cost and hybrid rice farmer in Central Lampung regency; while introduction of prime seed technology is not significantly effects toward productivity improvement and pesticide cost in hybrid rice field.  In fact, hybrid rice productivity in Central Lampung regency increase about 7,088% and hybrid rice pesticide cost increase about 6,84%  in comparison with inhybrid rice.  Because of introduction of hybrid seed technology implicated to some components of production cost, income, and other production factors, it is suggested to give an assistance to farmers as seed costumer, by private or governmental sector, so their productivity can be reached suitably to that potency.